Knowledge on Irradiation, Medical Imaging Prescriptions, and Clinical Imaging Referral Guidelines among Physicians in a Sub-Saharan African Country (Cameroon) - Boniface Moifo; Ulrich Tene; Jean Roger Moulion Tapouh; Odette Samba Ngano; Justine Tchemtchoua Youta; Augustin Simo; Joseph Gonsu Fotsin (Radiology Research and Practice)
Background. Clinical imaging guidelines (CIGs) are suitable tools to enhance justification of imaging procedures. Objective. To assess physicians’ knowledge on irradiation, their self-perception of imaging prescriptions, and the use of CIGs. Materials and Methods. A questionnaire of 21 items was self-administered between July and August 2016 to 155 referring physicians working in seven university-affiliated hospitals in Yaoundé and Douala (Cameroon). This pretested questionnaire based on imaging referral practices, the use and the need of CIGs, knowledge on radiation doses of 11 specific radiologic procedures, and knowledge of injurious effects of radiation was completed in the presence of the investigator. Scores were allocated for each question. Results. 155 questionnaires were completed out of 180 administered (86.1%). Participants were 90 (58%) females, 63 (40.64%) specialists, 53 (34.20%) residents/interns, and 39 (25.16%) general practitioners. The average professional experience was 7.4 years (1–25 years). The mean knowledge score was 11.5/59 with no influence of sex, years of experience, and professional category. CIGs users’ score was better than nonusers (means 14.2 versus 10.6; p<0.01). 80% of physicians (124/155) underrated radiation doses of routine imaging exams. Seventy-eight (50.3%) participants have knowledge on CIGs and half of them made use of them. “Impact on diagnosis” was the highest justification criteria follow by “impact on treatment decision.” Unjustified requests were mainly for “patient expectation or will” or for “research motivations.” 96% of interviewees believed that making available national CIGs will improve justification. Conclusion. Most physicians did not have appropriate awareness about radiation doses for routine imaging procedures. A small number of physicians have knowledge on CIGs but they believe that making available CIGs will improve justification of imaging procedures. Continuous trainings on radiation protection and implementation of national CIGs are therefore recommended.